Solid-liquid interface studies of titania and nanocarbon materials - Wang, C (2019)
Modifying TiO2 has been of great interest for applications in photocatalytic degradation of organic pollutants, production of hydrogen from water and photovoltaic applications. The chemical composition of TiO2 can be altered by doping by which the titanium and/or oxygen component is replaced. Doping alters the material’s optical properties, but sometimes at the cost of undesirable consequences.